A Comparative Histological Study of Skin in Clarias gariepinus and Oreochromis niloticus - Khairani, Shafia; Fikri, Faisal; Purnomo, Agus; Purnama, Muhammad Thohawi Elziyad (Universitas Airlangga, 2021)
This study aimed to evaluate the comparative of histological figures in Clarias gariepinus and Oreochromis niloticus skin. A total of 18 samples were observed and collected the skin preservation. The hematoxylin-eosin staining performed to determine the histological structure. Results showed that there were different structures in the epidermis and dermis layer between C. gariepinus and O. niloticus skin. Club cells showed dominated in the epidermis layer of C. gariepinus. The pigmented cell showed clearly in the basement layer of C. gariepinus compared to O. niloticus. Stratum compactum in O. niloticus also showed adequate compared to C. gariepinus.